Non-alcoholic fatty liver disease—A pilot study investigating early inflammatory and fibrotic biomarkers of NAFLD with alcoholic liver disease - Watt, Joanne; Kurth, Mary Jo; Reid, Cherith N.; Lamont, John V.; Fitzgerald, Peter; Ruddock, Mark W. (Frontiers in Physiology, 2022)
Non-alcoholic fatty-liver disease (NAFLD) is a condition where excess fat accumulates in the liver (hepatic steatosis) and there is no history of alcohol abuse or other secondary causes of chronic liver disease. NAFLD is a very common disorder, occurring in 25% of the global population. NAFLD is now the most common chronic liver disorder in Western countries. Liver biopsy is the gold standard for NAFLD diagnosis and staging; however, this is invasive, costly and not without risk. Biomarkers that could diagnose and stage disease would reduce the need for biopsy and allow stratification of patients at risk of progression to non-alcoholic steatohepatitis (NASH). One hundred and thirty-three patients were involved in the study (N=135: n=34 controls; n=26 simple steatosis; n=61 NAFLD/NASH, and n=14 alcoholic liver disease (ALD)). Clinically diagnosed (ICD-10) patient serum samples were obtained from Discovery Life Sciences (US) along with clinical history. Samples were run in duplicate using high-sensitivity cytokine array I, immunoassays and ELISAs. In total, n=20 individual biomarkers were investigated in this pilot study. Thirteen/20 (65%) biomarkers were identified as significantly different between groups; IFN, EGF, IL-1, IL-6, IL-8, IL-10, TNF, FABP-1, PIIINP, ST2/IL-33R, albumin, AST and ALT. Five/20 (25%) biomarker candidates were identified for further investigation; namely, three biomarkers of inflammation, IL-6, IL-8, and TNF, and two biomarkers of fibrosis, PIIINP and ST2/IL-33R. Single biomarkers are unlikely to be diagnostic or predictive at staging NAFLD due to the complex heterogeneity of the disease. However, biomarker combinations may help stratify risk and stage disease where patients are averse to biopsy. Further studies comparing the 5 biomarkers identified in this study with current diagnostic tests and fibrotic deposition in liver tissue are warranted.